Health risks associated with infertility and non-obstructive azoospermia - Eric Huyghe; Peter Ka-Fung Chiu (Asian Journal of Andrology)
Non-obstructive azoospermia is a common condition associated with significant health risks, including increased mortality, cancer, and chronic diseases such as metabolic and cardiovascular disorders. This review aims to highlight the potential health challenges faced by men with this condition compared to fertile counterparts. Through a comprehensive bibliographic search on PubMed, using the following algorithm: (“infertility, male” [MeSH Terms] OR “azoospermia” [MeSH Terms]) AND (“mortality” [MeSH Terms] OR “neoplasms” [MeSH Terms] OR “chronic disease” [MeSH Terms] OR “diabetes mellitus” [MeSH Terms] OR “heart diseases” [MeSH Terms]), we analyzed existing literature to explore the associations between infertility, specifically azoospermia, and adverse health outcomes. Findings indicate that infertile men are at a higher risk of death, various cancers (particularly testicular cancer), metabolic syndrome, diabetes, hypogonadism, and cardiovascular disease. Although research specifically addressing azoospermia is limited, available studies support the notion that men with this condition may experience heightened health vulnerabilities. Given these risks, it is imperative for healthcare professionals, especially urologists, to conduct thorough health assessments for men diagnosed with azoospermia. Informing patients of these potential health issues and integrating comprehensive evaluations into their care can facilitate early detection and intervention for life-threatening conditions. Ultimately, men with azoospermia should receive ongoing monitoring to address their specific health concerns, thus improving their long-term health outcomes.